RARE CASE OF LIPEMIA RETINALIS IN A 24 DAY OLD INFANT - RAJEETA BASUR; REENA KUMARI; DINESH KUMAR BHAGAT (Asian Journal of Pharmaceutical and Clinical Research, 2024)
We present a rare case of Lipemia Retinalis in a 24 day old Infant due Hyperlipoprotienimia type 1.